Regulation of adenovirus and cellular gene expression and of cellular transformation by the E1B-encoded 175-amino-acid protein. - Herbst, R S (1988)
Mutants of type 5 adenovirus that fail to express the E1B-gene-encoded 175-amino-acid (175R) protein are unable to morphologically transform primary or continuous cultures of rat embryo fibroblast cells. This phenotype could result from a direct effect of this E1B polypeptide (along with E1A polypeptides) on cellular gene expression resulting in a pathway leading to altered cell growth or from an indirect role of the 175R protein made possible by its ability to modulate viral early-gene (most likely E1A) expression. To distinguish between these two models, viruses were constructed that expressed the individual E1A 13S and 12S genes in the presence of either the E1B 175R or 495R protein. Regardless of the E1A gene product that was expressed, viruses that failed to express the E1B 175R protein were transformation defective. Additional studies suggest that the E1A 289R protein and E1B 495R protein function in a common pathway leading to the establishment of the transformed cell. We also observe that E3 gene expression by viruses that fail to express the E1A 289R protein affects the efficiency of focus formation. When tested in both nonpermissive CREF cells and permissive HeLa cells, the lack of 175R protein expression appeared to have no effect (a transient twofold decrease in E1A mRNA accumulation was observed in CREF cells) on viral early-gene expression. These results suggest that the initiation of the transformed cell phenotype occurs because of some interaction in a common pathway between the viral E1A proteins and E1B 175R protein. Furthermore, we have shown that the E1B 175R protein does not enhance the rate of transcription initiation from the mouse immunoglobulin heavy chain gene promoter when these sequences are localized on a viral genome, and it does not diminish the ability of the E1A proteins to decrease the rate of enhancer-dependent transcription.